Konsep Pola Asuh Orang Tua dalam Al-Qur’an: Studi Analisis Ayat-Ayat Komunikasi Orang Tua dan Anak - Abror, Pathil (Program Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2016)
This thesis is a study of the concept of parenting parents in the Koran (verses analysis study of communication parents and children), and aims to explore the type of parenting as well as the methods used by four parents in providing education and guidance to children became the object of this study. As for the four parents who meet the qualifications for being the object of this study are: As Noah and his sons; Prophet Ibrahim and Prophet Isma'il As; As the prophet Jacob and Joseph As well as Luqman and his son. By knowing parenting and methods used in the verse, it will be easier for parents to imitate and take lessons that are inside.This study is a pure research library using interpretation approach, using methods maudu'i. This method was chosen because it is considered the most appropriate, at least until recently, to study the concepts of Quran on an issue, if the expected results of comprehensive and intact. Because this study involves the Koran directly, the first source is the holy book of Quran. Manuscripts that are used are the manuscripts of Religious Affairs. Other sources include books of commentaries, books and other writings related to this research.The results showed that the type of parenting parents in the verses of communication parents and children have a pattern and pattern Authoritarian Democracy. Authoritarian pattern can occur when educators provide that pressure followed by learners, while pattern Democracy can walk when educators give students the freedom to think, be creative and not to impose to the learners. In addition, another result of this study is the existence of several methods used to instill the values contained in the QS. Hud (11) Verses 42-43, QS. Alsaffat (37) Verses 102, QS. Yusuf (12) Verses 4-5, QS. Luqman (31) Verses 13-19) are: a) the method of behavior, b) the method of mau'izahhasanah, c) the method of meeting , d) the method of attention.This research, contributing positively in spreading the wisdom-the wisdom of Quran learn how to ducate children well and help to answer everyday issue within the family so that cen createsakinah mawaddah wa rahmah.